The diverse roles of C-type lectin-like receptors in immunity - Scur, Michal; Parsons, Brendon D.; Dey, Sayanti; Makrigiannis, Andrew P. (Frontiers in Immunology, 2023)
Our understanding of the C-type lectin-like receptors (CTLRs) and their functions in immunity have continued to expand from their initial roles in pathogen recognition. There are now clear examples of CTLRs acting as scavenger receptors, sensors of cell death and cell transformation, and as regulators of immune responses and homeostasis. This range of function reflects an extensive diversity in the expression and signaling activity between individual CTLR members of otherwise highly conserved families. Adding to this diversity is the constant discovery of new receptor binding capabilities and receptor-ligand interactions, distinct cellular expression profiles, and receptor structures and signaling mechanisms which have expanded the defining roles of CTLRs in immunity. The natural killer cell receptors exemplify this functional diversity with growing evidence of their activity in other immune populations and tissues. Here, we broadly review select families of CTLRs encoded in the natural killer cell gene complex (NKC) highlighting key receptors that demonstrate the complex multifunctional capabilities of these proteins. We focus on recent evidence from research on the NKR-P1 family of CTLRs and their interaction with the related C-type lectin (CLEC) ligands which together exhibit essential immune functions beyond their defined activity in natural killer (NK) cells. The ever-expanding evidence for the requirement of CTLR in numerous biological processes emphasizes the need to better understand the functional potential of these receptor families in immune defense and pathological conditions.